2014
DOI: 10.1186/1752-1947-8-334
|View full text |Cite
|
Sign up to set email alerts
|

The retrieval of unerupted teeth in pedodontics: two case reports

Abstract: IntroductionThe retrieval of unerupted teeth in pedodontics is always significant to preserve the trophism of adjacent tissues, establish the correct space, provide adequate function and maintain good esthetics for the patient. The treatment plan is based on radiographic examinations and measurements, and on an accurate clinical evaluation; it aims to achieve the best treatment possible depending on the complexity of the specific case.In the most difficult clinical cases it is very important to have an early d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Among the possible alterations of the UFM position, the occurrence of a mesiopalatal rotation in the previous literature seems to reach a prevalence of 83% in a population of subjects with presence of malocclusion [5][6][7], or even higher in subjects with class II malocclusion where it ranges from 83% to 95% [5,[8][9][10]. Some authors hypothesized that the rotation itself could influence the correct occlusion with the lower first molar, generating a class II malocclusion [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Among the possible alterations of the UFM position, the occurrence of a mesiopalatal rotation in the previous literature seems to reach a prevalence of 83% in a population of subjects with presence of malocclusion [5][6][7], or even higher in subjects with class II malocclusion where it ranges from 83% to 95% [5,[8][9][10]. Some authors hypothesized that the rotation itself could influence the correct occlusion with the lower first molar, generating a class II malocclusion [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…While in the present study a significant decrease in crowding was observed after treatment with SA, there are no previous data in the literature about the changes of lower dental arch dimensions after a treatment with this appliance. Looking at the present results, SA seems to be more effective with respect to the LB in achieving a higher increase in the intercanine dimension, with possible clinical implications in the prevention of the lower canine impaction [28,29].…”
Section: Discussionmentioning
confidence: 54%
“…It is important to identify different anomalies and conditions to ensure the correct diagnosis and as a consequence the best approach to be adopted. Many conditions already have specific treatments discussed in the literature with high scientific evidence indices, with no relevant or contradictory questions related [10,13]. Moreover, the case described it does not fit into any classifications of diseases or conditions discussed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the time the cause for non-eruption of primary tooth is the presence of a mechanical obstacle, not anatomical, in its trajectory. It is fairly described in literature the association of lesions suchs as odontogenic tumors, cysts and non-neoplastic proliferative lesions (odontoma, cementoblastoma, adenomatoid odontogenic tumor, radicular cysts) with impacted primary teeth [2,6,[10][11][12][13]. Chronology may be modified by factors already discussed, and primary tooth remains impacted by the presence of permanent tooth that have a premature eruption.…”
Section: Discussionmentioning
confidence: 99%